2012
DOI: 10.3109/0886022x.2012.664809
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Calcium Oral Coadministration in Gentamicin-Induced Nephrotoxicity in Rats

Abstract: Frequent therapeutical use of an aminoglycoside antibiotic gentamicin (GM) is limited by its nephrotoxic effects often characterized by both morphological and functional alterations of kidney leading to acute renal failure. The aim of this study was to examine the effect of dietary calcium supplementation on GM-induced nephrotoxicity in rats. Experiments were performed on 30 adult male Wistar rats divided into three groups of 10 animals each. G-group received GM intraperitoneally at a dose of 100 mg/kg; GCa-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…GEN induced considerable elevation in the serum level of renal function biochemical indices, including BUN and Cr, thus illustrating the early damage of the renal filtration barrier. These findings verify the previous reports that GEN induced the renal damage in rats [17]. Similar to the previous studies, this investigation confirmed the protective effect of flavonoids against GEN [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…GEN induced considerable elevation in the serum level of renal function biochemical indices, including BUN and Cr, thus illustrating the early damage of the renal filtration barrier. These findings verify the previous reports that GEN induced the renal damage in rats [17]. Similar to the previous studies, this investigation confirmed the protective effect of flavonoids against GEN [18,19].…”
Section: Discussionsupporting
confidence: 82%
“…The most studied effect is necrosis of tubular epithelial cells. There is also a description of morphological glomerular damage with reduced function (Stojiljkovic et al, 2012[85]). The application of some drugs (gentamicin, cisplatin) to experimental animals is causing significant reduction in kidney blood flow and glomerular filtration with increase in vascular resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin (GM), one of aminoglycosides, is recommended as the first line antibiotic for many and life-threatening diseases because of its clinical effectiveness, a low rate of resistance and reasonable cost [5].Most studies report gentamicin nephrotoxicity rates of between 8% and 26% [6]. No helpful medications improve survival, restrain damage or fasten recovery from gentamicin induced AKI other than dialysis.…”
Section: Introductionmentioning
confidence: 99%